Artificial Intelligence in Legal Cases (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Modern leap in development Artificial Intelligence (AI) has led to its widespread application in various fields, including the legal sphere. The use of intelligent virtual assistants and other types of AI tools raises questions that will transform the legal profession. This article briefly describes the various ways in which AI can be applied in legal practice to assist lawyers and other legal professionals in their work. It provides a statistical overview and examples of current solutions used by lawyers, and scenarios in which AI tools can perform tasks traditionally performed by lawyers. As AI continues to integrate into legal practice, it raises some legal and ethical issues related to the integrity of the legal system, the duties of lawyers, and the protection of client rights.